Question

×-2y=17 3x-1y=31

160

likes798 views

Corbin

4.6

86 Answers

1. Multiply the first equation by 1:

x - 2y = 17

2. Multiply the second equation by 2:

6x - 2y = 62

3. Subtract the first equation from the modified second equation:

6x - 2y - (x - 2y) = 62 - 17

5x = 45

x = 9

4. Substitute \( x = 9 \) back into the first equation:

9 - 2y = 17

-2y = 8

y = -4

Answer:

x = 9, \; y = -4

2. Multiply the second equation by 2:

3. Subtract the first equation from the modified second equation:

4. Substitute \( x = 9 \) back into the first equation:

Answer:

Frequently asked questions (FAQs)

What is the area of a triangle with side lengths of 5, 12, and 13 using Heron's Formula?

+

What is the y-coordinate of the point where the cubic function f(x) = x^3 intersects the y-axis?

+

Question: Using the Fundamental Theorem of Calculus, find the derivative of ∫(0 to x) (t^2 + 3t + 1) dt.

+

New questions in Mathematics